Stable mixed chimerism after T cell-depleted allogeneic hematopoietic stem cell transplantation using conditioning with low-dose total body irradiation and fludarabine - Görner, Martin; Kordelas, Lambros; Thalheimer, Markus; Luft, Thomas; Pfeiffer, S.; Ustaoglu, Ferman; Punzel, Michael; Weber-Nordt, Renate; Moos, Marion; Goldschmidt, Hartmut; Ho, Anthony Dick (Bone marrow transplantation, 2002)
Although reduced intensity conditioning (RIC) before allografting is associated with low treatment-related morbidity and mortality, graft-versus-host disease (GVHD) remains a significant complication of hematopoietic stem cell transplantation (HSCT). T cell depletion (TCD) has been successfully used in conventional allotransplantation to reduce the incidence of GVHD, but was associated with an increased rate of engraftment failure. In a small cohort of six patients at high risk of developing GVHD we have determined whether sustained engraftment could be achieved using reduced intensity conditioning and T cell depletion in combination. All patients engrafted and 5/6 developed high levels (ie ⩾95%) of donor chimerism, even though mismatched related or matched unrelated donors were used. Only one patient developed acute GVHD, as he received donor lymphocyte infusions (DLI) for relapse. In summary, TCD might be a useful prophylactic tool in RIC allogeneic HSCT. Although TCD after RIC might be associated with high relapse rate, as 5/6 patients are not in remission, this combined strategy might be appropriate for patients with less aggressive malignant or non-malignant diseases in which high transplant-related morbidity and mortality is not acceptable.